2006
DOI: 10.1038/sj.cr.7310119
|View full text |Cite
|
Sign up to set email alerts
|

Functional analysis of a cotton glucuronosyltransferase promoter in transgenic tobaccos

Abstract: The 5' fragment (1 647 bp) of the cotton glucuronosyltransferase gene (GhGlcAT1) was transcriptionally fused to the b-glucuronidase (GUS) gene, and functionally analyzed for important regulatory regions controlling gene expression in transgenic tobacco plants. GUS activity analysis revealed that the full-length promoter drives efficient expression of the GUS gene in the root cap, seed coat, pollen grains and trichomes. Exposure of the transgenic tobacco to various abiotic stresses showed that the promoter was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 47 publications
0
16
0
Order By: Relevance
“…In this study, four groups of fiber development genes were identified: first group, ESTs that were generated from fiber cell, investigated by microarray or RT-PCR function profiling, and confirmed enrichment expression during fiber development, including up-regulation and down-regulation genes [18], [48]; second group, individual genes that were not only confirmed by microarray expression, but also were transformed to Arabidopsis or tobacco to verify their function by complementation test [35], [67], [81], [82]; third group, transcription factors, including MYB family, AP2/EREBP family, and GARP-G2-like transcription factors [36], [38]; and last group, genetically mapped fiber-derived EST gene candidates [40], [41], [44]. All four groups of genes were collected from previous publications and their sequences were downloaded based on the accession numbers from NCBI http://www.ncbi.nlm.nih.gov/or collected from dissertation text (Dr. Hassan's dissertation, Texas A&M University library).…”
Section: Methodsmentioning
confidence: 99%
“…In this study, four groups of fiber development genes were identified: first group, ESTs that were generated from fiber cell, investigated by microarray or RT-PCR function profiling, and confirmed enrichment expression during fiber development, including up-regulation and down-regulation genes [18], [48]; second group, individual genes that were not only confirmed by microarray expression, but also were transformed to Arabidopsis or tobacco to verify their function by complementation test [35], [67], [81], [82]; third group, transcription factors, including MYB family, AP2/EREBP family, and GARP-G2-like transcription factors [36], [38]; and last group, genetically mapped fiber-derived EST gene candidates [40], [41], [44]. All four groups of genes were collected from previous publications and their sequences were downloaded based on the accession numbers from NCBI http://www.ncbi.nlm.nih.gov/or collected from dissertation text (Dr. Hassan's dissertation, Texas A&M University library).…”
Section: Methodsmentioning
confidence: 99%
“…When introduced in tobacco however, many of these genes show an expression profile which includes trichome cells but is otherwise poorly specific. For example, the promoters from the cotton fiber genes SUS3 (Ruan et al 2009), GhRGP1 , GhGlcAT1 (Wu et al 2007), GhGAL1 also confer expression in vascular tissues, roots, flowers and cotyledons. Other promoters such as the cotton LTP3 (Liu et al 2000;Hsu et al 2005) and LTP6 (Hsu et al 1999) genes show specificity to the whole glandular trichomes of tobacco (Nicotiana tabacum), but do not differentiate between the secreting cells and the cells of the trichome stalk.…”
Section: Glandular Trichome Specific Terpene Synthases In the Solanaceaementioning
confidence: 98%
“…Applying electrophoretic mobility shift assay, Liu JingYuan's group [14] revealed that a transcription factor encoded by a cotton DREB1/CBFlike gene had a specific binding activity with the previously characterized DRE element and DRE-like sequence in the promoter of the dehydration-responsive late embryogenesis-abundant gene LEA D113, suggestive of a role in low temperature, drought and high salinity resistance. They also studied the expression patterns of several cotton genes, including a reversibly glycosylated polypeptide gene and a glucuronosyl transferase gene, in tobacco cells using the β-galactosidase reporter system [15][16][17] .…”
Section: Gene Cloning and Functional Analysismentioning
confidence: 99%